The tangible tele-meeting system for effective remote human communication - Lee, H.-J.; Jeong, M.-H.; You, B.-J. (39th International Symposium on Robotics, ISR 2008, 2008)
The virtual reality technology publishes many results, for example video game, 3D virtual movie, interface of computer and virtual meeting. However, the virtual reality has some restrictions that user neither can touch objects nor feels like what we feel in the real world. Also user should wear some heavy equipment to make user feel reality. Furthermore, these equipments are too expensive to use people. Recently, many researchers make effort to overcome restrictions of virtual reality using the robot technology or huge display instruments. However, these approaching still can't touch others or it wears heavy equipments. We proposed a new system which is called the Tangible telemeeting system. It overcomes the restrictions of virtual reality. The user wears only see-through-HMD, and the user can touch 3D objects using the humanoid robot. The Tangible tele-meeting system links human with robots with cyber space by using the multi-view camera, a humanoid robot and network technology. When the user communicates with the other using the Tangible tele-meeting system, the user can use all senses which relate communication. It becomes more effective than other virtual meeting systems.